2021
DOI: 10.5468/ogs.20186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lymphadenectomy on the treatment of endometrial cancer using data from the JSOG cancer registry

Abstract: Regional lymph node (LN) dissection is a standard surgical procedure for endometrial cancer, but there is currently no clear consensus on its therapeutic significance. We aimed to determine the impact of regional LN dissection on the outcome of endometrial cancer. Methods Study subjects comprised 36,813 patients who were registered in the gynecological tumor registry of the Japan Society of Obstetrics and Gynecology, had undergone initial surgery for endometrial cancer between 2004 and 2011, and whose clinicop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
4
2
2
Order By: Relevance
“…In contrast, Saotome et al recently reported significantly better overall survival rates in patients who had undergone systematic lymph node dissection. However, the above mentioned study differed markedly from others in respect of group sizes (only 27% of all patients had no lymphadenectomy), age, and FIGO stages [34].…”
Section: Discussioncontrasting
confidence: 59%
“…In contrast, Saotome et al recently reported significantly better overall survival rates in patients who had undergone systematic lymph node dissection. However, the above mentioned study differed markedly from others in respect of group sizes (only 27% of all patients had no lymphadenectomy), age, and FIGO stages [34].…”
Section: Discussioncontrasting
confidence: 59%
“…In contrast, Saotome et al recently reported signi cantly better overall survival rates in patients who had undergone systematic lymph node dissection. However, the above mentioned study differed markedly from others in respect of group sizes (only 27 % of all patients had no lymphadenectomy), age, and FIGO stages [33].…”
Section: Discussioncontrasting
confidence: 59%
“…Despite recent updates in the guidelines, many clinicians still do not feel comfortable replacing conventional LND with SLN mapping in high-risk patients. Additionally, the risk of lymph node metastasis was much higher in this cohort, as high as 20–30%, compared to the 5% observed in patients with low-risk subtype [ 11 13 ]. Furthermore, alternative lymphatic drainage, resulting in isolated para-aortic lymph node involvement is concerning [ 14 ].…”
Section: Introductionmentioning
confidence: 60%